Birth Weight in the Long-Run - Prashant Bharadwaj; Petter Lundborg; Dan-Olof Rooth (Institute for the Study of Labor (IZA), 2015)
We study the effect of birth weight on long-run outcomes, including permanent income, income across various stages of the lifecycle, education, social benefits take-up, and adult mortality. For this purpose, we have linked a unique dataset on nearly all Swedish twins born between 1926-1958, containing information on birth weight, to administrative records spanning nearly entire life time labor market histories. We find that birth weight positively affects permanent income and income across large parts of the life cycle, although there is some evidence of a fade out after age 50. Our results indicate that lower birth weight children are more likely to avail of social insurance programs such as unemployment and sickness insurance and that birth weight matters for adult mortality. We supplement our main analysis with more recent data, which enables us to study how the impact of birth weight on income and education of young adults has changed across cohorts born almost 50 years apart.
Keywords: I10; I18; 330; birth weight; early life; permanent income; unemployment sickness absence; life-cycle; mortality